MICROSURGERY IN A TERTIARY HOSPITAL IN EAST KALIMANTAN: A FIVE-YEAR RETROSPECTIVE STUDY FROM PLASTIC SURGERY DIVISION - Swantara, Devina; Ardan, Andi; Yudhy Arius; Selmy Sabry Mohamed Awad (Jurnal Rekonstruksi dan Estetik, 2025)
Highlights: This is the first comprehensive epidemiological analysis of microsurgical cases in East Kalimantan, filling a critical data gap outside Java. Complex soft-tissue defects accounted for 93.5% of cases, all managed with free flap transfer, predominantly anterolateral thigh and radial forearm flaps. The observed free flap success rate of 77.5% demonstrates functional microsurgical capacity at a provincial hospital and highlights targets for improving perioperative monitoring and outcomes.   Abstract: Introduction:  Microsurgery is a critical pillar of modern reconstructive surgery, enabling restoration of complex tissue defects. Data on its demography and outcome in East Kalimantan remains unavailable, limiting strategic service planning. This study aimed to describe the perioperative variables and outcome of microsurgical cases at a provincial referral hospital. Methods: A retrospective study was conducted at the Plastic, Reconstructive, and Aesthetic Surgery Division of Abdoel Wahab Sjahranie Hospital. All patients who underwent microsurgery between January 2020 and December 2024 were included via total sampling. Medical records were reviewed to extract demographic characteristics, referral sources, primary diagnoses, surgical procedures, and free flap outcomes. Results: A total of 31 surgery in 28 patients, with fluctuating annual distribution (highest in 2020, lowest in 2022). Most patients were male (64.5%) and adults aged 18–60 years (80.7%), predominantly referred from type B hospitals (61.3%). The most frequent diagnosis was complex soft-tissue defects (93.5%), with malignancy, post-burn contracture, chronic wounds, and electrical trauma as leading etiologies. All reconstructions employed free flap transfer with overall success rate was 77.5%, predominance of anterolateral thigh flap (58.1%). Conclusion: Microsurgical cases at Abdoel Wahab Sjahranie Hospital primarily involved young-to-middle-aged males with complex soft-tissue defects, managed with free flap reconstruction. These findings affirm the hospital’s role as a regional microsurgical referral center and highlight the need for strengthened perioperative monitoring and service expansion beyond trauma-related reconstruction.